A target-triggered and self-calibration aptasensor based on SERS for precise detection of a prostate cancer biomarker in human blood. Issue 16 (9th April 2021) - Wu, Qiong; Chen, Guannan; Qiu, Sufang; Feng, Shangyuan; Lin, Duo
Abstract : A target-triggered and self-calibration aptasensor based on SERS was developed for precise detection of a prostate cancer biomarker in human blood. Abstract : Sensitive and precise detection of prostate-specific antigen (PSA) is critical for prostate cancer screening and monitoring. Herein, a target-triggered and self-calibration aptasensor based on a core–satellite nanostructure using surface-enhanced Raman spectroscopy (SERS) technology was developed for the sensitive and reliable determination of PSA protein, with a limit of detection of 0.38 ag mL −1 and a dynamic detection range of 10 −2 to 10 −15 mg mL −1 . Furthermore, the proposed approach for the detection of PSA in patient blood samples was performed, and results showed that it is capable of providing comparable detection accuracy associated with a larger dynamic detection range and a lower detection limit as well as less sample requirement (only 5 μL) in comparison with the clinical commonly used method. Therefore, this SERS-based aptasensor for the detection of PSA in human blood samples has promising potential to be an alternative tool for clinical application in the accurate screening of prostate cancer.